Total Knee Arthroplasty following Knee Arthroscopy in Patients over 50 - Buck, J. Stewart; Odum, Susan M.; Salava, Jonathan K.; Macknet, David M.; Fehring, Thomas K.; Springer, Bryan D. (The Journal of Knee Surgery, 2021)
The purpose of this study was to evaluate the conversion rate of knee arthroscopy to ipsilateral total knee arthroplasty (TKA) within 2 years in patients aged 50 or older at the time of arthroscopy. The administrative database from a large, physician-owned orthopaedic practice (>100 surgeons) was queried to identify patients over the age of 50 who had undergone arthroscopic knee surgery between January 1, 2006 and January 2, 2015. The subset of patients who converted to TKA within 2 years after knee arthroscopy was identified and matched by age and sex to a control population that did not convert to TKA. Rates of conversion to TKA were calculated. Prearthroscopic digital radiographs were reviewed and Kellgren–Lawrence (KL) grades were compared among case and control populations. Univariable analyses and multivariable regression analysis were performed. Eight hundred seven of 16,061 (5.02%) patients aged 50 or older were converted to TKA within 2 years following ipsilateral knee arthroscopy. In univariable analysis, the rate of conversion to TKA in patients aged between 50 and 54 was 2.94%, compared with 4.44% in patients aged between 55 and 64, and 8.32% in patients 65 or older (p < 0.0001). Female sex was associated with a higher rate of conversion to TKA in univariable analysis (5.93 vs. 4.02% in males, p < 0.0001). KL grades were higher among patients who converted to TKA compared with those who did not (p < 0.0001). In a multivariable regression model controlling for age, sex, and KL grade, only increased KL grade was associated with increased odds of conversion to TKA. In the appropriately selected older patient, the risk of conversion to TKA within 2 years of knee arthroscopy is low (∼5%). Patients with KL grade 2 or higher at the time of arthroscopy should be counseled on the increased odds of early conversion to TKA.
Keywords: knee osteoarthritis; knee arthroplasty; knee arthroscopy